A Secure Parking System for Residential Area using IoT - Karim, Izz Fahmi; Ab Rahman, Tasiransurini (Evolution in Electrical and Electronic Engineering, 2023)
Reasonable and affordable prices increase the sale of apartments in Malaysia. The same goes for vehicles. The ability to own apartments and vehicles has indirectly led to an increase in the use of parking lot in apartments, where parking lot become fully occupied. Therefore, A Secure Parking System for Residential Area using IoT has been developed to overcome this issue. The term secures used in this project refers to how the project can guarantee a parking space for each resident from being taken over by others. In this project, the Arduino NANO 33 IoT with Wi-Fi Module is used to facilitate the connection to the Arduino IoT platform. This project is implemented as a prototype in a residential area where the prototype's size is determined by using a 1:64 scale car. The dashboard was built to make it easier for users to access their parking space. Each dashboard will be handed over to the owner of the parking space and directly to the apartment occupant by including the apartment occupant's email. The project achieved all the objectives where the system successfully secured the parking space of residents by applying a private dashboard that contains a virtual switch and providing an RFID Module to open the barrier by controlling the servo motor.